Mitochondrial phylogeny within the Yellow Chat (Epthianura crocea) does not support subspecific designation of endangered Alligator Rivers population. Issue 7 (24th July 2022) - Leppitt, Robin; Rose, Alea; Houston, Wayne A.; Kyne, Peter M.; Banks, Sam C.; Woinarski, John C. Z.; Garnett, Stephen T.
Abstract: The delineation of subspecies is important in the evaluation and protection of biodiversity. Subspecies delineation is hampered by inconsistently applied criteria and a lack of agreement and shifting standards on how a subspecies should be defined. The Australian endemic Yellow Chat ( Epthianura crocea ) is split into three subspecies ( E. c . crocea, E. c. tunneyi, and E. c. macgregori ) based on minor plumage differences and geographical isolation. Both E. c. tunneyi (Endangered) and E. c. macgregori (Critically Endangered) are recognized under Australian legislation as threatened and are the subject of significant conservation effort. We used mitochondrial DNA to evaluate the phylogeny of the Yellow Chat and determine how much genetic variation is present in each of the three subspecies. We found no significant difference in the cytochrome b sequences (833 base pairs) of E. c. crocea and E. c. tunneyi, but approximately 0.70% or 5.83 bp difference between E. c macgregori and both E. c. crocea and E. c. tunneyi. This analysis supports the delineation of E. c. macgregori as a valid subspecies but does not support separation of E. c. crocea from E. c. tunneyi . We also found very low levels of genetic variation within the Yellow Chat, suggesting it may be vulnerable to environmental change. Our results cast doubt upon the geographic isolation of E. c. crocea from E. c. tunneyi, but more advanced genetic sequencing and a robust comparison of plumage are needed to fully resolve taxonomy. Abstract : The Yellow Chat Epthianura crocea has an unsettled taxonomic history, with particular doubt over the delineation of the threatened E. c. tunneyi from E. c. crocea . We found no difference in the mitochondrial DNA of these two subspecies, casting doubt on their geographical isolation.